2021
DOI: 10.1111/pce.14141
|View full text |Cite
|
Sign up to set email alerts
|

Jujube witches' broom phytoplasma effectors SJP1 and SJP2 induce lateral bud outgrowth by repressing the ZjBRC1‐controlled auxin efflux channel

Abstract: Comprehensively controlling phytoplasma‐associated jujube witches' broom (JWB) disease is extremely challenging for the jujube industry. Although the pathogenesis of phytoplasma disease has been highlighted in many plant species, the release of lateral buds from dormancy under JWB phytoplasma infection has not been characterized in woody perennial jujube. Here, two 16SrV‐B group phytoplasma effectors, SJP1 and SJP2, were experimentally determined to induce witches' broom with increased lateral branches. In viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 54 publications
0
41
0
Order By: Relevance
“…Experimental characterization of the two ‘ Ca . P. ziziphi’ SAP11 homologs demonstrated that both can stimulate lateral bud outgrowth for witches’ broom symptoms when expressed in Nicotiana benthamiana ( Zhou et al, 2021 ). Intriguingly, in phytoplasma-infected jujube plants, these two SAP11 homologs have different expression patterns among tissue types.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental characterization of the two ‘ Ca . P. ziziphi’ SAP11 homologs demonstrated that both can stimulate lateral bud outgrowth for witches’ broom symptoms when expressed in Nicotiana benthamiana ( Zhou et al, 2021 ). Intriguingly, in phytoplasma-infected jujube plants, these two SAP11 homologs have different expression patterns among tissue types.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental characterization of the two SAP11 homologs in ‘ Ca . P. ziziphi’ demonstrated that both can stimulate lateral bud outgrowth for witches’ broom symptoms when expressed in Nicotiana bentha miana (Zhou et al, 2021). Intriguingly, in phytoplasma-infected jujube plants, these two SAP11 homologs have different expression patterns among tissue types.…”
Section: Resultsmentioning
confidence: 99%
“…The relatively small number of metabolic genes contrasts with the presence of numerous secreted effector proteins [ 15 , 18 , 19 , 20 ]. Effectors decrease the plant’s defenses [ 21 ] or alter its development [ 20 , 22 , 23 , 24 , 25 ] and promote the attractiveness of the plant to insect vectors [ 26 , 27 , 28 ]. These secreted effectors possess a signal peptide on the N-terminal side that may be confused with a transmembrane domain [ 29 ].…”
Section: Introductionmentioning
confidence: 99%